Interaction and Confrontation of Islamic Civilization with Christian Civilization Post Eastern Roman Conquest in Europe - Rinawati, Rinawati (Universitas Islam Negeri Sumatera Utara, 2024)
For Christian nations, the fall of Constantinople symbolized the collapse of their defensive stronghold and highlighted the threat posed by the Islamic Ottoman Empire. This event marked the transition from the center of Christian civilization to Islamic civilization, sparking a process of adaptation and interaction between the two civilizations. This paper examines how this interaction took place, including the integration and conflicts recorded in history and their impacts up to the present day. The research method used is a literature study, where the author traces relevant documents with a focus on the study. After finding the relevant sources, the researcher reads and critically analyzes them to understand their content, evaluate their validity, and reliability. The research results show that the relationship between Islam and Christianity during the Ottoman Empire demonstrated complex dynamics, with a mixture of tolerance, cooperation, and conflict. Policies of tolerance and cultural exchange had a positive impact on the development of civilization in the region. However, confrontations between the two religions arose from various factors, such as: Differences in beliefs and traditions became sources of tension, especially in the Balkan region. Political rivalry between the Ottomans and European Christian powers impacted inter-religious relations. Both Christian and Islamic parties discriminated against minority religions. The conflicts and tensions that emerged are also part of history that needs to be studied to understand the complexity of inter-religious relations in the past.